Предмет: Математика,
автор: AMIRSULIN
(7×+3)-(5×-7)=(2×-5)-(3×-6)
Ответы
Автор ответа:
0
Пошаговое объяснение:
(7х+3)-(5х-7)=(2х-5)-(3х-6)
7х+3-5х+7=2х-5-3х+6
7х-5х-2х+3х=-5+6-3-7
3х= -9
х= -9:3
Х = -3.
_____
((7*(-3)+3))-((5*(-3)-7))=((2*(-3)-5))-((3*(-3)-6))
7*(-3)+3-5*(-3)+7=2*(-3)-5-3*(-3)+6
-21+3+15+7=-6-5+9+6
4=4
Ответ: Х= -3.
Похожие вопросы
Предмет: Алгебра,
автор: xloyanruz
Предмет: Русский язык,
автор: Аноним
Предмет: Қазақ тiлi,
автор: akmaralkatas
Предмет: Биология,
автор: deadponies
Предмет: Биология,
автор: 4567ап